PENIS CANCER PROFILE IN PATIENTS RESIDENT IN MINAS GERAIS - Norrany Alves Ferreira da Silva, Kemberly; Ferreira Coutinho, Cinara; Cristiny Mendes Viana, Larissa; Antunes Teixeira, Nadine; Pego Batista , Leidaiane; Oliveira Facin Souza, Dienypher; Oliveira Silva, Letícia (Health and Society, 2021)
Introduction: Penile cancer are rare neoplasms, being more frequent in men aged 50 years or older, although it may affect men of any age. Unfavorable socioeconomic conditions, poor intimate hygiene, HPV infections, among others, are risk factors for this type of cancer. Objective: To know the profile of penile cancer in patients living in the state of Minas Gerais, Brazil. Methods: A descriptive study of quantitative approach was conducted through data from patients diagnosed with penile cancer in hospital records of the José Alencar Gomes da Silva National Cancer Institute (INCA). Results and discussion: In the period from 2015 to 2019, 573 diagnoses of penile cancer were recorded in the database of the José Alencar Gomes da Silva National Cancer Institute (INCA). Conclusion: Men aged between 50 and 74 years, married, brown and with incomplete high school were identified, the main occupation was agricultural worker. It is essential that in order to face this problem, men’s health is considered routinely and systematically in the routine health services.